Research on Magnetic Flux Detection Technology for Shallow Sea Moving Targets. Issue 1 (December 2020) - Huang, Kui; Xu, Chaoqun; Yi, Zhong; Zhang, Shaohua; Meng, Lifei
Abstract: The ocean moving target is covered by the vast ocean, and it is highly concealed. In order to effectively detect the moving target in the ocean, based on the theory of magnetic flux induction, the characteristics of the detected target are analysed, the equivalent magnetic model of the target is established, and the rectangular induction coil structure is designed. The coil structure was optimized by studying the effects of coil size parameters and moving target motion parameters on induced electromotive force. Finally, through field trials, using induction coils to collect and analyse the signals of wooden boats, speedboats and kayaks, the feasibility of the detection technology was verified, which provided a new way for the detection of shallow sea moving targets.